2017
DOI: 10.1371/journal.pone.0187557
|View full text |Cite
|
Sign up to set email alerts
|

The role of H19, a long non-coding RNA, in mouse liver postnatal maturation

Abstract: H19 RNA is highly expressed at early postnatal ages and precipitously decreases at a specific time corresponding with increases in expression of genes important for mature liver function, such as drug metabolizing enzymes. H19’s role in the regulation of liver maturation is currently unknown. Using an H19 knockout mouse model to determine the role of H19 in liver development, we quantified gene expression for insulin growth factor signaling, Wnt signaling, key cytochrome P450 (P450) enzymes known to change as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…48 It was reported that deletion of a nuclease-sensitive region between the Igf2 and H19 genes led to Igf2 misregulation and increased adiposity. 50 One important aspect of biological functions for H19 is to regulate lineage-specific differentiation of MSCs. Subconfluent mouse hepatocyte iHPx cells were infected with Ad-H19, Ad-siH19, Ad-siMlxipl, Ad-H19 + Ad-siMlxip or Ad-RFP for 36 h. The infected hepatocytes were collected and subcutaneously injected into the flanks of athymic nude mice for 10 d. Masses at the injection sites were retrieved, fixed and snap-frozen or paraffin embedded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 It was reported that deletion of a nuclease-sensitive region between the Igf2 and H19 genes led to Igf2 misregulation and increased adiposity. 50 One important aspect of biological functions for H19 is to regulate lineage-specific differentiation of MSCs. Subconfluent mouse hepatocyte iHPx cells were infected with Ad-H19, Ad-siH19, Ad-siMlxipl, Ad-H19 + Ad-siMlxip or Ad-RFP for 36 h. The infected hepatocytes were collected and subcutaneously injected into the flanks of athymic nude mice for 10 d. Masses at the injection sites were retrieved, fixed and snap-frozen or paraffin embedded.…”
Section: Discussionmentioning
confidence: 99%
“…H19 may regulate hepatic lipid metabolism through at least two pathways, the mTOR signalling axis and Mlxipl-regulated transcription network in hepatocytes possibly resulted from activating Wnt/β-catenin and/or IGF2 signalling pathways. 50 One important aspect of biological functions for H19 is to regulate lineage-specific differentiation of MSCs. We found that H19 plays an important role in regulating BMP9-regulated lineage-specific differentiation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Igf2 and H19 are adjacent, imprinted genes [74] that show aberrant imprinting and epigenetic abnormalities in HCC [29]. H19 is highly expressed in proliferative tissues, including liver regeneration after injury [74], and its first exon encodes miR-675, whose overexpression promotes liver cancer [62]. The strong up regulation of these three genes in female E1/E2-KO livers suggests E1/E2-KO female mice may show increased susceptibility to HCC compared to wild-type female liver in response to CCl 4 and other hepatotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…These genes include Igf2, H19 and miR675 (Fig 7E, S11 Table ). Igf2 and H19 are adjacent, imprinted genes [67] that show aberrant imprinting and epigenetic abnormalities in HCC [29]. H19 is highly expressed in proliferative tissues, including liver regenerating after injury [67], and its first exon encodes miR-675, whose overexpression promotes liver cancer [50].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Igf2 and H19 are adjacent, imprinted genes [67] that show aberrant imprinting and epigenetic abnormalities in HCC [29]. H19 is highly expressed in proliferative tissues, including liver regenerating after injury [67], and its first exon encodes miR-675, whose overexpression promotes liver cancer [50]. The strong up regulation of these three genes in E1/E2-KO female liver suggests female E1/E2-KO mice may show increased susceptibility to liver toxicity and HCC compared to female wild-type mice, e.g., in response to hepatotoxins such as carbon tetrachloride.…”
Section: Plos Geneticsmentioning
confidence: 99%